2012
DOI: 10.5267/j.msl.2011.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing effects of service encounter quality on customer satisfaction in banking industry

Abstract: Service quality represents a modern approach for quality in enterprises and organizations and serves the development of a truly customer-focused management and culture. Measuring service quality offers an immediate, meaningful and objective feedback about clients' preferences and expectations. In this paper, we study the relationship between customer perceptions from service encounter quality and loyalty of customer to organization and employees. The proposed study is implemented for banking sector in Iran usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
0
10
0
3
Order By: Relevance
“…As a distribution area of the questionnaires, the premises of the hospital were excluded, given the emotional burden of hospitalized patients, associated with positive or negative instantaneous events or the disease that could temporarily affect their perception of quality, positively or negatively. As Oliver (1989) and Gazor et al (2012) report, satisfaction is defined as a value, emotional response. Therefore, customers can evaluate the subject after interpreting it.…”
Section: Methods Of Collecting Datamentioning
confidence: 99%
“…As a distribution area of the questionnaires, the premises of the hospital were excluded, given the emotional burden of hospitalized patients, associated with positive or negative instantaneous events or the disease that could temporarily affect their perception of quality, positively or negatively. As Oliver (1989) and Gazor et al (2012) report, satisfaction is defined as a value, emotional response. Therefore, customers can evaluate the subject after interpreting it.…”
Section: Methods Of Collecting Datamentioning
confidence: 99%
“…This difference was attributed to similar differences between customer perception and customer expectations about banking service quality. Gazor et al (2012) also sought to examine the influence of service quality on the satisfaction of customers in the financial service industry, as well as the relationship between service quality perceptions and customer loyalty to financial institution employees and organizations. An analysis of the questionnaire surveys found that financial service quality was the most desirable factors among customers in terms of satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Expectations play important role to determine the consumer's service quality evaluation and satisfaction (O'Connor et al, 2000). Therefore, many organizations extremely consider service quality to obtain their customers' satisfaction and loyalty (Gazor et al, 2012). Business managers must always listen very carefully to what their customers say as a good feedback to improve the quality of the services.…”
Section: Introductionmentioning
confidence: 99%
“…Service quality (SERQUAL) is a modern technique for measuring quality in different enterprises and organizations and serves the development of a truly customer-focused management and culture (Gazor et al, 2012). Web-based service quality, on the other hand, is a method for measuring the quality of services provided based on the web technology such as online communication, purchase and delivery of products/services (Cronin & Taylor, 1992).…”
Section: Introductionmentioning
confidence: 99%